2003
DOI: 10.1046/j.1471-8286.2003.00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of microsatellites in the Asian walking catfish Clarias macrocephalus

Abstract: Microsatellite loci were characterized in the walking catfish, Clarias macrocephalus, random clones from a small genomic library using a (GT)15 probe. Primers for DNA amplifications using polymerase chain reaction (PCR) were designed and synthesized for 23 loci. Twelve loci were polymorphic, with the number of alleles ranging from two to 13 alleles per locus. Developed microsatellite primers should prove useful for population studies and genetic mapping of the walking catfish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
0
7
2
Order By: Relevance
“…blast results showed that all microsatellite loci identified in this study did not have significant similarity with sequences from the previous efforts by Sukmanomon et al . (2003).…”
Section: Characterization Of 16 Polymorphic Microsatellite Loci For Ccontrasting
confidence: 74%
“…blast results showed that all microsatellite loci identified in this study did not have significant similarity with sequences from the previous efforts by Sukmanomon et al . (2003).…”
Section: Characterization Of 16 Polymorphic Microsatellite Loci For Ccontrasting
confidence: 74%
“…Of 30 polymorphic loci, 16 contained dinucleotide repeats and 14 contained compound repeats (Table A1). BLAST results showed that all microsatellite loci developed in this study did not have significant similarity to the sequences in the public databases ( E ‐value >10 −4 ) including sequences from the previous efforts by Na‐Nakorn et al (1999) and Sukmanomon et al (2003).…”
Section: Resultsmentioning
confidence: 77%
“…Thirty loci were developed in this study. Twenty‐six loci were reported previously including 12 loci developed from a genomic library (Sukmanomon et al 2003) and 14 loci identified from the EST sequences of walking catfish (Sukkorntong et al 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2004) found that genetic introgression not only occurred in central Thailand but also in the Mekong River basin and southern part of Thailand. In Peninsular Malaysia, anecdotal evidence also suggests there is genetic introgression between C. gariepinus and C. macrocephalus and as such warrants further investigation on this issue using nuclear markers such as microsatellites (Sukmanomon et al., 2003; Yue et al., 2003).…”
Section: Discussionmentioning
confidence: 99%